Product Quality Monitoring of Shewhart Chart Based on Function Integration for Manufacturing Factory. Issue 4 (August 2019) - Tang, Dan; TanLi, Mengqing; Jiang, Yan; Wan, Xiang; Peng, Rushu
Abstract: This paper summarizes the mathematic principle of Shewhart chart, and gives a description of cutting and machining error for analysis of variety of manufacturing error. The approach of function integration of product quality monitoring using Shewhart chart is discussed in detail for manufacturing factory, which emphases the function integration with category tree. And the development of product quality monitoring software is investigated finally.